Clinical Value of Noncontrast‐Enhanced Radial Quiescent‐Interval Slice‐Selective (QISS) Magnetic Resonance Angiography for the Diagnosis of Acute Pulmonary Embolism Compared to Contrast‐Enhanced Computed Tomography and Cartesian Balanced Steady‐State Free Precession. Issue 5 (14th June 2020) - Salehi Ravesh, Mona; Tesch, Karolin; Lebenatus, Annett; Koktzoglou, Ioannis; Edelman, Robert R.; Eden, Matthias; Langguth, Patrick; Graessner, Joachim; Jansen, Olav; Both, Marcus
Abstract : Background: Free‐breathing noncontrast‐enhanced (non‐CE) magnetic resonance angiography (MRA) techniques are of considerable interest for the diagnosis of acute pulmonary embolism (APE), due to the possibility for repeated examinations, avoidance of side effects from iodine‐based contrast agents, and the absence of ionizing radiation exposure as compared to CE‐computed tomographic angiography (CTA). Purpose: To analyze the clinical performance of free‐breathing and electrocardiogram (ECG)‐gated radial quiescent‐interval slice‐selective (QISS)‐ MRA compared to CE‐CTA and to Cartesian balanced steady‐state free precession (bSSFP)‐ MRA. Study Type: Prospective. Subjects: Thirty patients with confirmed APE and 30 healthy volunteers (HVs). Field Strength/Sequence: Radial QISS‐ and bSSFP‐MRA at 1.5T. Assessment: Signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) were computed to compare the pulmonary imaging quality between MRA methods. The pulmonary arterial tree was divided into 25 branches and an ordinal scoring system was used to assess the image quality of each pulmonary branch. The clinical performance of the two MRA techniques in accurately assessing APE was evaluated with respect to CE‐CTA as the clinical reference standard. Statistical Tests: Wilcoxon signed‐rank and Spearman's correlation tests were performed. Sensitivity and specificity of the MRA techniques were determined using CE‐CTA as the clinical reference standard. Results: Thrombus‐mimicking artifacts appeared more frequently in lobar and peripheral arteries of patients with Cartesian bSSFP than with radial QISS‐MRA (pulmonary trunk: 12.2% vs. 14.0%, P = 0.64; lobar arteries: 35.6% vs. 22.0%, P = 0.005, peripheral arteries: 74.4% vs. 49.0%, P < 0.001). The relative increases in SNR and of CNR provided by radial QISS‐MRA with respect to Cartesian bSSFP‐MRA were 30–35% ( P ‐values of SNR/CNR, HVs: 0.09/0.09, patients: 0.03/0.02). The image quality of pulmonary arterial branches was considered good to excellent in 77.2% of patients with radial QISS‐MRA and in 43.2% with Cartesian bSSFP‐MRA ( P < 0.0001). The clinical performance of radial QISS‐MRA was higher than Cartesian bSSFP‐MRA for grading embolism, with a total sensitivity of 86.0% vs. 80.6% and a specificity of 93.3% vs. 84.0%, respectively. Data Conclusion: Radial QISS‐MRA is a reliable and safe non‐CE angiographic technique with promising clinical potential compared to Cartesian bSSFP‐MRA and as an alternative technique to CE‐CTA for the diagnosis of APE. Level of Evidence: 1 Technical Efficacy Stage: 3